We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+2
201
2
avatar+322 

Use the half-angle formulas to simplify the expression.

 

 

sqrt((1 + cos(26x)) /2)

 Dec 2, 2018
 #1
avatar+171 
+2

The simplified answer is: −sin(x−12) cheeky

 Dec 2, 2018
 #2
avatar+101046 
+1

\(cos(2*13x)=cos^2(13x)-sin^2(13x)\\ cos(2*13x)=cos^2(13x)-(1-cos^2(13x))\\ cos(2*13x)=2cos^2(13x)-1\\ \frac{cos(2*13x)+1}{2}=cos^2(13x)\\ so\\ \frac{1+cos(26x)}{2}=cos^2(13x)\\ \sqrt{\frac{1+cos(26x)}{2}}=\sqrt{cos^2(13x)}\\ \sqrt{\frac{1+cos(26x)}{2}}=cos(13x)\\ where \quad cos(13x) \ge 0\)

.
 Dec 3, 2018

9 Online Users